1987
DOI: 10.1111/j.2044-8325.1987.tb00266.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of age and education on perceptions of occupational attractiveness

Abstract: This study rcprcscnts an effort to dctcrmine the diffcrcntial erects of agc and education on pcrccptions of occupational attractivcncss. A total of463 respondents ranging from high school scniors to collcgc seniors rated the attractivencss of 41 job dimensions. Rcsults indicated significant indepcndcnt elTccts for both age and education on attractiveness ratings. An analysis ofcovariancedcmonstrated that education had a significant clTcct while agc did not, suggesting that education is thc more important influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 4 publications
(3 reference statements)
1
2
0
Order By: Relevance
“…However, there was little indication that this trend reflected a shift towards more realistic focussing of concern. Overall, the variable of school type seemed somewhat more influential than age in determining job preference and job choice, consistent with some recent U.S. findings which suggest that type/amount of secondary education received plays a more critical role than age per se in determining young people's ratings of occupational attractiveness (Fields and Shallenberger, 1987).…”
Section: Discussionsupporting
confidence: 74%
“…However, there was little indication that this trend reflected a shift towards more realistic focussing of concern. Overall, the variable of school type seemed somewhat more influential than age in determining job preference and job choice, consistent with some recent U.S. findings which suggest that type/amount of secondary education received plays a more critical role than age per se in determining young people's ratings of occupational attractiveness (Fields and Shallenberger, 1987).…”
Section: Discussionsupporting
confidence: 74%
“…There are a lot of other factors that could contribute to perceiving an occupation as attractive. The dimensions of job attractiveness are competency, self-direction, interpersonal relations, extrinsic outcomes and intrinsic outcomes (Fields & Shallenberger, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Fields & Shallenberger (1987) studied a 295 FRED FROST cross-sectional sample of university and high school students. They concluded that education rather than age plays the more critical role in determining what an individual rates as attractive about an occupation.…”
mentioning
confidence: 99%